Application of low temperature storage of Mastura (J37) jackfruit bulbs on ice confectionery processing - Mat Johari, Amiruddin (2019)
Jackfruit is one of the major fruits planted in Malaysia. However, the Pahang State Farmers Association (PASFA) reported that the Mastura jackfruit variety faced wastage issue due to unutilized surplus. Vacuum packaging technique of jackfruit bulbs under low temperature and jackfruit ice cream processing were proposed to PASFA to solve this problem. Therefore, the aims of this study were: (i) to investigate the effects of refrigerated and deepfrozen vacuum-packed Mastura jackfruit bulbs on the physico-chemical properties of jackfruit ice cream; (ii) to identify the properties of jackfruit ice cream formulated with different concentrations of Mastura jackfruit puree; (iii) to compare the factory-scaled and laboratory-scaled ice cream production. Vacuum-packed bulbs were stored in refrigeration and deepfreeze storages. Deep-frozen vacuum-packed bulbs retained better bioyield point (1.05±0.06N), colour (L*: 55.72±0.75), total soluble solid (16.4±0.3°Brix), titratable acidity (0.0619±0.0037%), ripening index (265) and microbial count (6x102cfu/ml) up to 3 weeks of storage. Refrigerated vacuum-packed bulbs retained good bio-yield point (2.58±0.07N), colour (L*: 54.62±0.19), total soluble solid (17.3±0.3°Brix), titratable acidity (0.0277±0.0370%), ripening index (629) and microbial count (52x102cfu/ml) until 3 weeks of storage only. The blanching process of bulbs was optimized using Response Surface Methodology. The blanching parameters i.e. the temperature and time were optimized based on minimized firmness and colour of bulbs. The optimum parameter for jackfruit bulbs blanching were at 4 min and 78°C. The qualities of jackfruit ice creams formulated with refrigerated and deep-frozen vacuum-packed bulbs were measured. The melting characteristics, overrun, and hardness of jackfruit ice cream formulated with refrigerated vacuum-packed jackfruit bulbs of different storage times (0-3 weeks) showed consistent qualities. Similar progress was observed for ice cream formulated with deep-frozen vacuum-packed jackfruit bulbs (0-6 weeks). The optimum jackfruit puree concentration in Mastura jackfruit ice cream was determined to be 20% (JF20) of the total mass of ice cream mix. JF20 ice cream was able to withstand higher force of compression (27.79kPa) compared to JF10 (21.15kPa) and JF30 (10.48kPa). JF20 also scored a higher overall liking (4.25±0.55) compared to JF10 (3.30±0.57) and JF30 (3.35±0.67). Finally, the studies of Mastura jackfruit bulbs and jackfruit ice cream properties were used for the development of the jackfruit ice cream production line. The production line was able to process 100 to 120 litres of ice cream within 8 hours. The factory-scaled Mastura jackfruit ice cream had an overrun of 82% while laboratory-scaled jackfruit ice cream had an overrun of 56%. The Overall Equipment Efficiency (OEE) of the factory on the 1st day and 2nd to 5th day of the week were 58.4% and 70%, respectively. The information gathered in this research could help reduce wastage of Mastura jackfruit generated from the surplus and increase the demand of jackfruits with new value-added products.